Peran Brand Image Dalam Mendorong Minat Beli Konsumen Pada Toko Geox Gandaria City - Nabila Putri Miranto; Putri Handayani; Fuji Putri Pratiwi; Amanda Putri Syakilla; Devi Fitrianingsih; Muhamad Aji Fahrezy; Derizka Inva Jaswita (Jurnal Intelek Insan Cendikia, 2026)
This study aims to analyze the role of brand image in driving consumer purchasing interest at the Geox Gandaria City store. This study uses a qualitative approach with descriptive methods. Data collection techniques were carried out through in-depth interviews with consumers and store employees, direct observation at the research location, and supporting documentation. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The results show that Geox product quality, including aspects of comfort, durability, design, and material, has a positive influence on consumer purchasing interest   Keywords: Brand Image, Purchase Interest, Geox